2020
DOI: 10.1101/2020.04.23.20077099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving reporting standards for polygenic scores in risk prediction studies

Abstract: Over the past decade, genome-wide association studies have identified genetic variation associated with a wide range of human diseases and traits. These findings are now commonly aggregated into polygenic risk scores, which can bridge the gap between the initial discovery efforts and clinical applications for disease risk estimation. However, there is remarkable heterogeneity in the reporting of these risk scores due to a lack of accepted standards for the development, reporting, and application of PRS. This l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 69 publications
(96 reference statements)
2
97
0
Order By: Relevance
“…Finally, it is important to acknowledge that commercial clinical testing of PGS has already begun [ 16 ▪▪ ]. Lipid PGS and ASCVD prediction are key first areas for commercialization, given the public health significance and anticipated actionability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it is important to acknowledge that commercial clinical testing of PGS has already begun [ 16 ▪▪ ]. Lipid PGS and ASCVD prediction are key first areas for commercialization, given the public health significance and anticipated actionability.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Clinical Genomics Resource (ClinGen) consortium and European Bioinformatics Institute's Polygenic Score Catalog have created a joint statement (termed ‘PRS-RS’) on recommended reporting standards for PGS [ 16 ▪▪ ]. This effort builds on foundational reporting standards in genetic risk prediction [ 17 ] and multivariable prediction models for individual prognosis or diagnosis [ 18 ].…”
Section: Reporting Standards For Polygenic Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the AUC/R 2 could be based upon resources such as The Polygenic Score (PGS) Catalog (Lambert et al, 2021), which collate polygenic score data and corresponding prediction metrics. To support this effort, future polygenic score risk prediction studies should follow suggested reporting standards (Wand et al, 2021). Thirdly, for continuous phenotypes, the approach is tailored to normally distributed phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…There is widespread variability in PGS research, even with regard to nomenclature: they can be referred to as genetic or genomic scores, and as polygenic risk scores (PRS) or genomic risk scores (GRS) if they predict a discrete phenotype (such as a disease) 24 . There are also many approaches to derive PGS using individual level genotype data or GWAS summary statistics 25 .…”
Section: Main Textmentioning
confidence: 99%